2022
DOI: 10.1002/cbdv.202200243
|View full text |Cite
|
Sign up to set email alerts
|

Three New Pregnanes Isolated from the Cynanchum auriculatum

Abstract: Three new compounds named cynansteroid A (1), cynansteroid B (2) and cynansteroid C (3), together with nine known C21‐steroidal pregnane sapogenins (4–12) were isolated from the hydrolytic extract of the roots of Cynanchum auriculatum. The structures of cynansteroid A–C (1–3) were ascertained via the detailed analysis of the HR‐ESI‐MS, 1D and 2D NMR, and the calculated and experimental ECD data of cynansteroid B (2). Compound 11 displayed moderate inhibitory activity toward Verticillium dahliae Kleb (IC50=37.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…The antifungal activities of 1–18 were evaluated against three phytopathogenic fungi at 50 μg/mL in vitro with hymexazol and thiophanate‐methyl as the positive controls, including R. solani , M. oryzae , and Phomopsis sp [30] . The results ( Figure 3, Table S1 ) indicated that compounds 3 , 4 , 8 , 10 , 11 , 12 , 13 , and 18 revealed noticeable antifungal activities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The antifungal activities of 1–18 were evaluated against three phytopathogenic fungi at 50 μg/mL in vitro with hymexazol and thiophanate‐methyl as the positive controls, including R. solani , M. oryzae , and Phomopsis sp [30] . The results ( Figure 3, Table S1 ) indicated that compounds 3 , 4 , 8 , 10 , 11 , 12 , 13 , and 18 revealed noticeable antifungal activities.…”
Section: Resultsmentioning
confidence: 99%
“…The antifungal activity in vitro of all compounds were tested by the following procedure with a slightly modified as previously reported. [30,34,35] Each tested compound (1 mg) dissolved in DMSO (20 μL), was added to 10 mL potato dextrose agar (PDA) medium to prepare 90 mm PDA plates. And then, a 5 mm diameter of each fungus tested was put onto the middle of mixed PDA plates, fostered at 28 °C for 3-5 days.…”
Section: In Vvitro Antifungal Activity Assaymentioning
confidence: 99%
“…The inoculated PDA plates were incubated at 28±1 °C for 4–6 days. The EC50 was determined for compounds at five different concentrations [26–28] . Based on the test of in vitro antifungal activity, compound C17 against Phomopsis sp .…”
Section: Methodsmentioning
confidence: 99%
“…The EC50 was determined for compounds at five different concentrations. [26][27][28] Based on the test of in vitro antifungal activity, compound C17 against Phomopsis sp. was further tested in vivo on kiwifruit.…”
Section: Fungimentioning
confidence: 99%
“…[1,2] C 21 -steroidal glycosides, as typical constituents of C. otophyllum, demonstrate a variety of pharmacological activities, including antitumor, antivirus, immunosuppressive, antiaging, and antidepressant properties. [3][4][5][6][7] Recently, much effort had been made to research the chemical composition of the acid hydrolysate of Cynanchum plants to obtain novel and potent biological active C 21 -steroidal sapogenins, [8][9][10][11][12] especially anticancer activity. [13 -16] Our previous phytochemical investigation resulted in the isolation of nine new C 21 -steroidal sapogenins (cynotogenins AÀ I) and several C 21 -steroidal sapogenins with significant anticancer activity from the acid hydrolysate of C. otophyllum, and the structure-activity relationships (SARs) was discussed.…”
Section: Introductionmentioning
confidence: 99%